2016
DOI: 10.1155/2016/9026573
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune Activation Profiles of HIV-1 Subtype C-Infected Children and Their Mothers

Abstract: Little is known about immune activation profiles of children infected with HIV-1 subtype C. The current study compared levels of selected circulating biomarkers of immune activation in HIV-1 subtype C-infected untreated mothers and their children with those of healthy controls. Multiplex bead array, ELISA, and immunonephelometric procedures were used to measure soluble CD14 (sCD14), beta-2 microglobulin (β2M), CRP, MIG, IP-10, and transforming growth factor beta 1 (TGF-β1). Levels of all 6 biomarkers were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…Worryingly, however, several studies have reported that even in the face of administration of virally suppressive HAART for periods of 6–12 months, circulating levels of both Tregs and TGF-β1 remained elevated. This appears to be consistent with ongoing chronic immune activation and its associated risks of persistent, albeit of lesser magnitude, immunosuppression, and development of HIV-associated, non-AIDS-defining conditions ( 6 , 7 , 51 53 ).…”
Section: Role Of Tgf-β1 In Hiv Infection-associated Immunosuppressionsupporting
confidence: 66%
See 2 more Smart Citations
“…Worryingly, however, several studies have reported that even in the face of administration of virally suppressive HAART for periods of 6–12 months, circulating levels of both Tregs and TGF-β1 remained elevated. This appears to be consistent with ongoing chronic immune activation and its associated risks of persistent, albeit of lesser magnitude, immunosuppression, and development of HIV-associated, non-AIDS-defining conditions ( 6 , 7 , 51 53 ).…”
Section: Role Of Tgf-β1 In Hiv Infection-associated Immunosuppressionsupporting
confidence: 66%
“…As mentioned above, increases in the concentrations of TGF-β1 in the circulation of HIV-1 infected patients have been reported in several studies, and, in one of these, were found to be highly correlated with increased numbers of circulating Tregs ( r = 0.921, p = 0.001) ( 52 ), indicating that the cytokine is likely to originate predominantly from Tregs. This contention is supported by findings that elevated numbers of circulating Tregs and concentrations of TGF-β1 correlate with increased levels of circulating biomarkers of chronic immune activation (monocyte- and lymphocyte-derived activation markers) and bacterial translocation ( 51 53 ). As mentioned earlier, these are considered to be major drivers of immunosuppression and progression to AIDS ( 3 5 , 62 ).…”
Section: Role Of Tgf-β1 In Hiv Infection-associated Immunosuppressionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the findings of two studies, South African HIV-infected participants, particularly males, like their European and North American counterparts, have high rates of cigarette smoking with frequencies of 52–71% recorded in males and 13–28% in females [34, 37, 53], with somewhat lower rates recorded in another study which was undertaken at the same HIV clinic as the current study [54].…”
Section: Discussionmentioning
confidence: 83%
“…The selection of biomarkers used in this study was based on previous findings with the inclusion of several additional markers [33, 34].…”
Section: Methodsmentioning
confidence: 99%